Formation of gene associations that code for general homeostasis and performance components of durum wheat (Triticum durum Desf.) - P. N. Malchikov; M. G. Myasnikova (Вавиловский журнал генетики и селекции, 2015)
Since 1912, durum wheat breeding in the Middle Volga region has passed several stages. Acceleration of the breeding process was observed during the period of joining gene pools from Bezenchuk (the Middle Volga region), Kharkov (Ukraine) and Saratov (the Lower Volga region), when the level of varietal adaptivity and productivity increased to the greatest extent. In this regard, the aim of our research was the evaluation of the impact of original parental genotypes on the building of the hereditary base of cultivars, as well as the demonstration of the formation and evolution of co-adaptive gene blocks of durum wheat in the Middle Volga region. To fulfil the tasks, diallelic analysis of yield elements, homeostatic characteristics of the trait “grain weight per plant” and cluster analysis of the pedigrees of modern cultivars were applied. The study showed that the process of durum wheat breeding was followed by the building of a co-adaptive gene block encrypting elements of plant performance and their homeostatic regulation by means of step-by-step evolution. Dominant genes with additive effects and maximal expression under drought and high temperatures prevailed in the structure of the polygenic system of co-adaptive block of modern cultivars. At the recent stage of breeding (1989–2013), germplasm development in the majority of cultivars bred at the Samara Research Institute of Agriculture occurred under strong influence of the Saratov gene pool, but it did not hamper the gene pool clustering according to germplasm similarity. The resulting clusters of varieties differed in the contribution of the “Saratov germplasm” to their heredity. This contribution was considered as weak (cluster A), moderate (cluster B) and strong (cluster C), corrected for different contributions of germplasms from other wheat accessions. The main inference from the results of the investigation is that at the modern stage it is necessary to extend the genetic basis of original material for durum wheat breeding in the Middle Volga region.